The effect of age on the VO2max response to high-intensity interval training - Støren, Ø.; Helgerud, J.; Sæbø, M.; Støa, E. M.; Bratland-Sanda, S.; Unhjem, R. J.; Hoff, J.; Wang, E. (Medicine & Science in Sports & Exercise, 2017)
Purpose: High-intensity interval training (HIIT) is documented to yield effective improvements in the cardiovascular system and be an excellent strategy for healthy aging. However, it is not determined how age may affect the training response of key components of aerobic endurance.